The Biotherapeutic Potential of Lactobacillus reuteri Characterized Using a Target-Specific Selection Process - Sagheddu, Valeria; Uggeri, Francesca; Belogi, Luisella; Remollino, Laura; Brun, Paola; Bernabè, Giulia; Moretti, Giancarlo; Porzionato, Andrea; Morelli, Lorenzo; Castagliuolo, Ignazio; Elli, Marina (Frontiers in Microbiology, 2020)
The growing body of clinical and experimental data support the view that the efficacy of probiotics is strain-specific and disease-specific. Thus, newly isolated probiotic strains should be disease- targeted. Therefore, we firstly characterized a novel strain of Lactobacillus reuteri LMG P-27481 for safety (sensitivity to antibiotics and genome analysis) and putative efficacy (resistance to gut transit, adhesiveness, induction of cytokines, release of antimicrobial metabolites) by the conventional in-vitro experimental approach proposed to identify beneficial microbes by national and international guidelines. Afterward, LMG P-27481 was submitted to in-vitro assays targeted on diarrhea (lactose utilization, inhibition of pathogens such as bacteria and Rotavirus) revealing a stronger ability, compared to well-known reference strains, to antagonize Clostridium difficile (CD). Final confirmation of LMG P-27481 features in controlling CD colitis was achieved by an in-vivo trial on mice conditioned with large spectrum antibiotics before receiving CD challenge. Two out of the 3 antibiotic-treated groups received daily the probiotic strain LMG P-27481 with different duration in order to simulate a preventive approach (probiotic administered prior to CD challenge) or an antagonistic approach (probiotic administered after CD challenge). LMG P-27481 administration, with either protocols, significantly reduced CD DNA concentration in caecum and C. difficile toxins titer in the gut lumen, as compared to untreated controls. Moreover, LMG P-27481 supplementation significantly mitigated body weight loss, extent of inflammatory infiltrate and tissue damage. Despite the requirement for further in-vivo assessments on humans, the selection and characterization process targeted to diarrhea and CD infection, described in this study, identify the strain L. reuteri LMG P-27481 as a promising probiotic candidate in the course of CD infection.